2013
DOI: 10.1136/bjophthalmol-2012-302779
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing on the retinal vascular responsiveness to flicker light in glaucoma patients and in ocular hypertension

Abstract: Vascular responsiveness to flicker light decreases with age in healthy individuals, in glaucoma patients and in OHT patients. This effect seems to be comparable between the tested groups, and age-related change in vascular responsiveness to flicker light seems an unlikely risk factor for glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
1
23
1
Order By: Relevance
“…In addition to endothelial dysfunction, ischemia-induced oxidative stress may interfere with normal pericyte behavior during microvascular dysfunction. 25,26 The effects of aging on retinal vessels have also been reported from other recent studies. Kneser et al described a significant decrease in the overall arterial regulative amplitude -defined as the sum of the maximum percentage dilatation and the maximum percentage constriction-and a significant decrease in constriction with age.…”
Section: Discussionmentioning
confidence: 68%
“…In addition to endothelial dysfunction, ischemia-induced oxidative stress may interfere with normal pericyte behavior during microvascular dysfunction. 25,26 The effects of aging on retinal vessels have also been reported from other recent studies. Kneser et al described a significant decrease in the overall arterial regulative amplitude -defined as the sum of the maximum percentage dilatation and the maximum percentage constriction-and a significant decrease in constriction with age.…”
Section: Discussionmentioning
confidence: 68%
“…Inclusion criteria were: best corrected visual acuity better than 20/25, refractive errors lower than 3 diopters of sphere and 2 diopters of cylinder, normal intraocular pressure (<18 mm Hg), normal appearance of the optic disc, normal visual field (the latter was examined with a SITA 24-2 standard test in all subjects using the Humphrey VF analyzer, HFA II 750-4.1 2005, Carl Zeiss Meditec Inc, USA), no significant ocular disease found by routine ophthalmological examination, no history of glaucoma in the family and/or systemic diseases with possible ocular involvement, such as diabetes. Controls were matched with patients for age and refractive error because these factors have been shown to influence OCT measurements2223. Moreover, because it has been shown that cigarette smoking leading to a significant increase in choroidal thickness up to 1 h after24, all the subjects had not smoked the hour before the examination.…”
Section: Methodsmentioning
confidence: 99%
“…; Gugleta et al. ). Nevertheless, a more complex analysis of the dynamics of both vasodilation and vasoconstriction responses, as well as of the capacity to re‐establish a preflicker diameter after the cessation of stress, is needed for a better understanding of healthy individual vascular dynamics.…”
Section: Introductionmentioning
confidence: 96%